Sustainability index analysis of microalgae cultivated in biorefinery palm oil mill effluent - A. Santoso; T. Handayani; D. Pinardi; K. Kusrestuwardani; N. Widyastuti; I. Djarot; J. Haryanti; A. Sitomurni; H. Apriyanto (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Palm oil mill effluent is a liquid waste produced at a palm oil mill industry during the production process containing abundant organic pollutants such as nitrogen and phosphorus that will be harmful to the environment. However, palm oil mill effluent as a nutrient for the growth of microalgae has the potential for pollutant removal as well as algae biorefinery products such as biofuel, functional food and many others. This research objectives to analyze the sustainability of the microalgae biomass production for bio-refinery based on the sustainability index assessment. METHODS: The primary data was compilated via the questionnaires to researchers in the community of microalgae as well as scientific judgment by experts as respondents. Data is processed and analyzed using the multidimensional scaling Rapfish program. Data analyzed was conducted by analyzing four dimensions: social, economic, ecological, and technological dimensions which consisting of 47 attributes.FINDINGS: The result showed that the sustainability index calculated was 73.53 percent (good), which indicates the process has the potential to be developed while paying attention to leverage factors in every dimension of the sector. Analysis of each dimension on the 4 dimensions shows that the environment dimension is lowest in 67.30 percent, while the economy, technology and social dimension are 70.99 percent, 73.67 percent and 82.17 percent, respectively. Some leverage attributes that require more attention in order to improve sustainability are management experience and skills (in environment dimension), involvement of family member (in the social dimension), the productivity level (in economic dimension), and management of experience and skill (technological dimention).CONCLUSION: Based on the prospective analysis, it is known that there are 4 key factors or dominant factors that are very influential in the microalgae supply system, namely production, productivity, land conversion, consumption per capita and population. It is still necessary to do further research for the utilization of microalgae biomass into value-added products with an optimal, technically, economically, environmentally and socially sustainable system. The study provides insights on the feasibility of the proposed sustainable concept in Indonesia for the government to arrange policies and programs.